Evidência de retardo no pico de desova da tartaruga de pente na costa sul do Rio Grande do Norte - Oliveira, Gabriel César dos Santos (2018)
The study of changes in the behavioral pattern of sea turtles is of fundamental importance for the conservation of the species. Eretmochelys imbricata, popularly known as a hawksbill turtle, is considered, according to the IUCN's red list, an animal with a high risk of extinction (critically endangered) both in Brazil and abroad. The objective of this study was to compare spawning peaks throughout the oviposition seasons for a period of ten years of data collection. In this work, analyzes were performed to show differences in the spawning period (E. imbricata) observed in the southern coast of Rio Grande do Norte (RN). The database (2006 to 2016) was analyzed to evaluate if there is a temporal displacement of the spawning period of E. imbricata. The spawn records computed daily within each season are visualized as a daily spawn histogram. In order to smooth the data to perform a better statistical analysis was made cumulative sum of data. An adjustment using the logistic curve was performed on the cumulative sum. Based on the spatial variation rate (derived) function calculated by the cumulative sum function and a Gaussian adjustment, the maximum spawning day for each season was estimated. A significant correlation was observed between occurrence peaks and spawning seasons. Using the Pearson's test, the statistical data were obtained (R = -0.70; df = 8; p = 0.024). The angular coefficient, calculated from the linear adjustment of the data, showed a delay of approximately 1.2 days per year, with error of ± 4,4, throughout the studied period. The data presented indicate the correlation between the change in the spawning period (temporal detachment) with probable resource variations and with global environmental changes due to climate change.